One new species of Hemielimaea Brunner von Wattenwyl from China - Song, Xi-Ming; Yuan, Li; Liu, Chun-Xiang (Zootaxa, 2012)
One new species Hemielimaea (Hemielimaea) adeviara sp. nov. from China is described. Characteristics of the stridulatory fileon underside of male left tegmen, male stridulatory area on left and right tegmen, and abdominal apex of male and female areprovided. Important and necessary illustrations of the new species are presented. The type specimens are deposited in Collections of Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS).